Angiogenic profiling in HELLP syndrome cases with or without hypertension and proteinuria. (December 2019) - Trottmann, Fabienne; Baumann, Marc; Amylidi-Mohr, Sofia; Surbek, Daniel; Risch, Lorenz; Mosimann, Beatrice; Raio, Luigi
Abstract: Objectives: Angiogenic profiling with the use of sFlt-1/PlGF ratio (soluble fms-like tyrosine kinase-1/placental growth factor) can be helpful to characterize women with signs of impending preeclampsia (PE). However, little is known about the angiogenic profile of pregnancies complicated by HELLP syndrome. The aim of this study was to examine the relationship of angiogenic profiles in cases of HELLP syndrome with and without classical signs of preeclampsia. Study design: The angiogenic profile of pregnant women with singleton gestation and isolated PE (group 1), PE associated with HELLP syndrome (group 2), and isolated HELLP syndrome (group 3) from 01/2011 to 03/2018, were compared. To overcome gestational age dependent angiogenic behavior, cases (group 3) were matched 1:2 with cases from group 1 and 2. Matching criteria was gestational age (±1 week). PE and HELLP syndrome were defined according to the international Society for the Study of Hypertension in Pregnancy (ISSHP) statement 2014. Results: During the observational period, 244 women could be included in the study. Of those, 237 (97.1%) were diagnosed with PE. In 42 cases (17.2%) PE was associated with HELLP syndrome while 7 (2.9%) patients were diagnosed with isolated HELLP syndrome. Angiogenic profiles in terms of sFlt-1/PlGF ratios differed significantly between the three groups, showing highest levels in group 2 (PE/HELLP) while cases with isolated HELLP demonstrated the lowest ratios and sFlt-1 values (p = 0.01). Conclusion: We conclude that isolated HELLP syndrome is rare and seems to be a particular entity expressing a different angiogenic behaviour compared to classical PE or PE associated with HELLP syndrome.